Armoring Youth for SDGs Implementation through the Collaboration between Youth and Policymaker - Adhipramana, Dama Rifki; Awwabina, Gina; Harinda, Sherly (Universitas Muhammadiyah Yogyakarta, 2020)
Sustainable Development Goals (SDGs) have set the purpose to tackle multiple problems and create well-being by 2030. The characteristic of youth as an agent of change and the flood of information is crucial for the implementation of SDGs. The contribution of youth is a catalyst for the better or for the worse result to achieve indicators and targets within SDGs. Using comparative analysis techniques, it shows that developed, developing, and least developed countries have a different priority that leads to different strategies in supporting the youth to carry out SDGs programs. This paper provides systematic identification of clashes and illustrates the different points of view between policymakers and the youth that become challenges for youth's contributions to supporting SDGs programs. Youth involvement is limited in politics, society, and economy, especially in the decision-making process. However, the number of youth's participation and the mechanism for youth's contributions predispose the accomplishment scales of SDGs. This paper emphasizes the need of raising awareness among the youths and better mechanisms to create collaboration between the youth and policymaker. Settling youth as representation to establish youth structures and programs wherewith armoring the youth to contribute onSDGs.